A lucky fall? Case report. - Chakera, A; Leslie, T; Roberts, I; O'Callaghan, C; Cranston, D (2010)
Renal cell carcinomas (RCCs) account for 3% of all solid neoplasms, with an increased incidence after renal transplantation. In transplant recipients, RCCs predominantly occur in the patient's native kidneys. Herein is reported a case of a localized RCC of recipient origin that developed in the donor allograft and was detected 8 years after renal transplantation. Treatment with high-intensity focussed ultrasound followed by partial nephrectomy was successful, averting the need for dialysis therapy.